PEMBELAJARAN DENGAN MEMPERHATIKAN ASPEK KEJIWAAN - Yahdi, Muhammad (Jurnal Pendidikan Kreatif, 2020)
Learning process both inside and outside the classroom, the teachers' concern is the students. The benefit of learning is not for the teacher but for the students. Every student is unique or special. The uniqueness and habits are usually shaped by the culture and interaction of students with their living environment. Learning process should always care the students' psychological aspects whether their talents, interests or knowledge developments. Teachers are required to do various learning strategy because the students taught have different aspects of psychology. There are several students easily understand the teachers' explanations, and some of them are slow to get it who need more guidance to know perfectly.